Frihamnskyrkan - Bergspredikan - (:unkn) unknown (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik, 2025)
The model shows an abstract version of the Sermon on the mount, which served as an inspiration to the architect when designing the church hall. Similar to its reference in the bible the goal was to gather many different people up on the ”hill” and listen to the sermon of the church.
Frihamnskyrkan - Sermon of the Mount
Keywords: Church; Frihamnen